The emergence of iPhone and its impact on mobile carriers and handset manufacturers: The case of USA, Europe and Japan - Shinichiro Terada (International Telecommunications Society (ITS), 2012)
This paper investigates the impact of iPhone, a representative of smartphones, on telecommunications carriers and handset manufacturers in U.S.A, Europe, and Japan. We choose the event study methodology to evaluate the impact of iPhone emergence. We also look at the financial profit of the carriers and manufacturers in order to confirm the financial impact of iPhone emergence. Our research question is How does the emergence of iPhone generate the impact on the telecommunications carriers and the handset manufactures in U.S.A, Europe and Japan? The results show that the impacts of iPhone present differently on the telecommunications carriers and the handset manufacturers. Regarding the impact on telecommunications carriers, 1) the results of event study show that the iPhone-affiliated-carriers, such as AT&T, Telefonica and Soft Bank, are neutral by the iPhone emergence, but non iPhone-affiliated-carriers have negative impact by the iPhone emergence. 2) the results of financial profits show that almost of all telecommunications carriers in U.S.A and Japan grow their profits after the iPhone emergence, but many of the telecommunications carriers in Europe reduce their profits after the iPhone emergence regardless of iPhone affiliation. Regarding the impact on handset manufacturers, the results of event study and financial profits show that 1) Apple, iPhone manufacture, have positive impact and grow profit by the iPhone emergence, but 2) many of other handset manufacturers have negative impact and reduce profit by the iPhone emergence.
Keywords: 330